A Rare Congenital Vascular Anomaly: A Case of Left-sided Inferior Vena Cava - Computed Tomography Findings - Koc, Mustafa; Kose, Evren; Sarsilmaz, Mustafa (Aves, 2012)
[Abstract Not Available]
Nadir bir konjenital vasküler anomali: Solda yerleşimli vena cava i?nferior-bilgisayarlı tomografi bulguları